PROSES BERPIKIR KREATIF SISWA TUNANETRA DALAM MENGKONSTRUK BANGUN DATAR BERBANTUAN ALAT PERAGA TANGRAM MENURUT TAHAPAN WALLAS - Arifani, Ulfa; Setiawan, Toto' Bara; Sunardi, Sunardi; Sugiarti, Titik; Monalisa, Lioni Anka (Department of Mathematics Education , University of Jember, 2019)
This study aims to describe the creative thinking process of blind students in constructing plane figure assisted by tangram props according to the stages of Wallas. The research subjects were three blind students of VIII grade SLB-TPA Negeri 1 Branjangan. Data collection methods used were test questions constructing plane figure and interviews. Based on the analysis of the results of tests and interviews shows that students of S1, S2, S3 through all the processes of creative thinking according to the Wallas’s stages include the preparation stage, the incubation stage, the illumination stage, and the verification stage when resolving problems constructing plane figure. At the preparation stage, blind students tend to lack understanding of the initial information such as explaining the problem given. At the incubation stage, blind students need a long time to do the process of pondering thinking about solving the problem in question. At the illumination stage, blind students are able to get two or more different ideas for completion. Blind students tend to use trial and error to find an idea. At the verification stage, blind students tend to re-check the answers obtained to reassure the answers are correct.